Content of Regional Library Communities on the VKontakte Social Network - N. A. Stepanova (Библиосфера, 2024)
Social networks are one of the platforms for posting official content and interacting with users, as well as providing remote access to information resources. The purpose of analyzing the content of communities in the VKontakte social network of the Oryol regional libraries (public, children’s and special) was to identify the structure and typology of communities, their characteristic features, and types of labels. The reason for choosing the accounts of regional libraries as the object of research was the social function they perform: regional libraries are the flagships of the development of the library system of a certain territory. The popularity of publications in communities was measured using the Engagement Rate coefficient. A direct correlation has been revealed between the type of publication and its popularity: the more popular the publication, the more publications of this type are posted in the community. For more effective functioning of library communities, it is necessary to develop a content plan that is based on the theory of management and marketing of social networks.